Effectiveness of Education Using Comic Media on Knowledge About Covid-19 Among Elementary School Students - Mansur, Arif Rohman; Sari, Ira Mulya; Herien, Yelly; Neherta, Meri; Chong, Mei Chan (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Children typically have a diminished capacity to comprehend the COVID-19 epidemic. To convey information about COVID-19 to elementary school students (ESS), it takes educational comic media that children like because it is “fun,” “informative“ and well-understood. However, the effectiveness of this intervention has yet to be thoroughly investigated. This study aimed to measure the knowledge of ESS after studying COVID-19 with comics. Methods: A pre-post quasi-experimental design with a control group was used in this study. There were 66 ESS recruited on purpose. Intervention (n = 33) and control (n = 33) groups were formed. The intervention group received COVID-19 education using comic book media. Who Will Win the Fight Between Kids, Vaayu, and Corona?, a COVID-19 Awareness Comic, was translated into Indonesian. The education was given twice every two weeks, while the standard school intervention was given to the control group. To collect data, researchers designed a questionnaire based on a literature study. The questionnaire was valid and reliable, with a Cronbach alpha of 0.71, and the results were analysed using the independent sample t-test. Results: There was a substantial difference in Knowledge towards COVID-19 ratings between the control and intervention groups (p = 0.001). The mean Knowledge towards COVID-19 score of the intervention group was higher than that of the control group (M=4.33 vs M=1.63). Knowledge about COVID-19 differed significantly between the intervention and control groups (p = 0.001). Conclusion: Comic books are effective in increasing knowledge about COVID-19 in ESS. REFERENCES Direktorat Jenderal Pencegahan Pengendalian Penyakit. Situasi Terkini Perkembangan Coronavirus Disease (COVID-19) 23 Maret 2020 » Info Infeksi Emerging Kementerian Kesehatan RI [Internet]. Info Infeksi Emerging Kementerian Kesehatan RI; 2020. Available from:https://covid19.kemkes.go.id/situasi-infeksi-emerging/info-corona-virus/situasi-terkini-perkembangan-coronavirus-disease-covid-19-23-maret-2020/ Corona Sumbarprov. SUMBAR TANGGAP CORONA [Internet]. 2020. Available from: https://corona.sumbarprov.go.id/ Unicef. Indonesia COVID-19 Response Situation Report [Internet]. 2022 [cited 2022 Dec 27]. Available from: https://www.unicef.org/media/129056/file/Indonesia-COVID-19-SitRep-September-2022.pdf Li Q, Guan X, Wu P, Wang X, Zhou L, Tong Y, et al. Early Transmission Dynamics in Wuhan, China, of Novel Coronavirus–Infected Pneumonia. New England Journal of Medicine [Internet]. 2020;0(0). doi: 10.1056/NEJMoa2001316 [Google Scholar] [PMC free article] [Pubmed] Irfan U. The risk Covid-19 poses for children, explained. Vox [Internet]. 2020 Mar 18; Available from: https://www.vox.com/2020/3/18/21181009/coronavirus-in-kids-symptoms-covid-19-risk Glenza J. Can kids catch coronavirus? What we know about Covid-19 and children. The Guardian [Internet]. 2020; Available from: https://www.theguardian.com/world/2020/mar/23/can-kids-catch-coronavirus-what-we-know-about-covid-19-and-children Zimmermann P, Curtis N. Coronavirus Infections in Children Including COVID-19: An Overview of the Epidemiology, Clinical Features, Diagnosis, Treatment and Prevention Options in Children. Pediatr Infect Dis J. 2020;39(5):355-368. doi: 10.1097/INF.0000000000002660.[<a href="https://scholar.google.com/scholar_lookup?title=Coronavirus+Infections+in+Children+Including+COVID-19%3A+An+Overview+of+the+Epidemiology%2C+Clinical+Features%2C+Diagnosis%2C+Treatment+and+Prevention+Options+in+Children&btnG=">Google Scholar][Pubmed] WHO. COVID-19 disease in children and adolescents: Scientific brief, 29 September 2021 [Internet]. 2021 [cited 2022 Dec 28]. Available from: https://www.who.int/publications-detail-redirect/WHO-2019-nCoV-Sci_Brief-Children_and_adolescents-2021.1 Liu W, Zhang Q, Chen J, Xiang R, Song H, Shu S, et al. Detection of Covid-19 in Children in Early January 2020 in Wuhan, China. New England Journal of Medicine [Internet]. 2020;0(0). doi:10.1056/NEJMc2003717[Google Scholar][Pubmed] Unicef. How teachers can talk to children about coronavirus disease (COVID-19 [Internet]. 2020. Available from: https://www.unicef.org/laos/stories/how-teachers-can-talk-children-about-coronavirus-disease-covid-19 Khaiwal R, Mor S. Kids, Vaayu, and Corona: Who Wilns The Fight? A Comic for Covid-19 Awareness. In: National Centre for Disease Control (NCDC. 2020. Harrison D. Desember 12). The importance of awareness. BelievePerform - The UK’s Leading Sports Psychology Website [Internet]. 2013. Available from: https://believeperform.com/the-importance-of-awareness/ Bhatia R. How to Talk to Your Anxious Child or Teen About Coronavirus [Internet]. 2020. Available from:https://adaa.org/learn-from-us/from-the-experts/blog-posts/consumer/how-talk-your-anxious-child-or-teen-about Grootens-Wiegers P, Vries MC, Beusekom MM, Dijck L, Broek JM. Comic strips help children understand medical research: Targeting the informed consent procedure to children’s needs. Patient Educ Couns. 2015;98(4):518-24. doi: 10.1016/j.pec.2014.12.005.[Google Scholar][Pubmed][Crossref] Hanson A, Drendel AL, Ashwal G, Thomas A. The Feasibility of Utilizing a Comic for Education in the Emergency Department Setting. Health Communication. 2017;32(5):529–32. doi: 10.1080/10410236.2016.1211076[Google Scholar][Pubmed] Mendelson A, Rabinowicz N, Reis Y, Amarilyo G, Harel L, Hashkes PJ, et al. Comics as an educational tool for children with juvenile idiopathic arthritis. Pediatr Rheumatol Online J. 2017 Sep 2;15(1):69. doi: 10.1186/s12969-017-0198-5.[Google Scholar][PMC free article] [Pubmed] Sinha I, Patel A, Kim FS, Maccorkle ML, Watkins JF. Comic books can educate children about burn safety in developing countries. J Burn Care Res. 2011;32(4):e112-117. doi: 10.1097/BCR.0b013e3182223c6f. [Google Scholar][Pubmed] Tekle-Haimanot R, Preux PM, Gerard D, Worku DK, Belay HD, Gebrewold MA. Impact of an educational comic book on epilepsy-related knowledge, awareness, and attitudes among school children in Ethiopia. Epilepsy Behav. 2016 Aug;61:218–23. doi: 10.1016/j.yebeh.2016.05.002[Google Scholar][Pubmed][Crossref] Lee F, Suryohusodo AA. Knowledge, attitude, and practice assessment toward COVID-19 among communities in East Nusa Tenggara, Indonesia: A cross-sectional study. Frontiers in Public Health [Internet]. 2022 [cited 2022 Nov 16];10. doi:10.3389/fpubh.2022.957630[Google Scholar][PMC free article] [Pubmed] Xue Q, Xie X, Liu Q, Zhou Y, Zhu K, Wu H, et al. Knowledge, attitudes, and practices towards COVID-19 among primary school students in Hubei Province, China. Child Youth Serv Rev. 2021 Jan;120:105735. doi: 10.1016/j.childyouth.2020.105735.[Google Scholar][PMC free article][Pubmed][Crossref] Mehraeen E, Oliaei S, SeyedAlinaghi S, Karimi A, Mirzapour P, Afsahi AM, et al. COVID-19 in Pediatrics: A Systematic Review of Current Knowledge and Practice. Infect Disord Drug Targets. 2022;22(5):47–57. doi: 10.2174/1871526521666210929121705.[Google Scholar][Pubmed] Kissler SM, Tedijanto C, Goldstein E, Grad YH, Lipsitch M. Projecting the transmission dynamics of SARS-CoV-2 through the postpandemic period. Science. 2020 Apr 14;eabb5793. doi: 10.1126/science.abb5793[<a href="https://scholar.google.com/scholar_lookup?title=Kissler+SM%2C+Tedijanto+C%2C+Goldstein+E%2C+Grad+YH%2C+Lipsitch+M.+Projecting+the+transmission+dynamics+of+SARS-CoV-2+through+the+postpandemic+period&btnG=">Google Scholar][PMC free article] [Pubmed] Hesse-Biber SN. Mixed Methods Research: Merging Theory with Practice. Guilford Press; 2010.[Google Scholar] Aleixo PA, Sumner K. Memory for biopsychology material presented in comic book format. Journal of Graphic Novels and Comics [Internet]. 2017;8(1):79–88. doi:10.1080/21504857.2016.1219957 [Google Scholar] Kearns C, Kearns N. The role of comics in public health communication during the COVID-19 pandemic. Journal of visual communication in medicine. 2020;43(3):139–49. doi: 10.1080/17453054.2020.1761248 [Google Scholar][Pubmed] Joshi A, Hillwig-Garcia J, Joshi M, Lehman E, Khan A, Llorente A, et al. Comics as an Educational Tool on a Clinical Clerkship. Acad Psychiatry. 2019 Jun;43(3):290–3. doi: 10.1007/s40596-018-1016-1 [Google Scholar][Pubmed] Ghia JE, Gaulin S, Ghia L, Garancher L, Flamand C. Informing children citizens efficiently to better engage them in the fight against COVID-19 pandemic. PLOS Neglected Tropical Diseases [Internet]. 04 Nov 20 [cited 2021 Apr 25];14(11):e0008828. doi:10.1371/journal.pntd.0008828[Google Scholar][PMC free article] [Pubmed] Callender B, Obuobi S, Czerwiec MK, Williams I. COVID-19, comics, and the visual culture of contagion. Lancet. 2020;396(10257):1061–3. doi: 10.1016/S0140-6736(20)32084-5.[Google Scholar] [PMC free article] [Pubmed][Crossref] Tjiam AM, Holtslag G, Van Minderhout HM, Simonsz-Tóth B, Vermeulen-Jong MHL, Borsboom GJJM, et al. Randomised comparison of three tools for improving compliance with occlusion therapy: An educational cartoon story, a reward calendar, and an information leaflet for parents. Graefe’s Archive for Clinical and Experimental Ophthalmology = Albrecht Von Graefes Archiv Fur Klinische Und Experimentelle Ophthalmologie [Internet]. 2013;251(1):321–9. doi:10.1007/s00417-012-2107-4[<a href="https://scholar.google.com/scholar_lookup?title=Randomised+comparison+of+three+tools+for+improving+compliance+with+occlusion+therapy%3A+An+educational+cartoon+story%2C+a+reward+calendar%2C+and+an+information+leaflet+for+parents&btnG=">Google Scholar][Pubmed] Gray DJ, Kurscheid J, Mationg ML, Williams GM, Gordon C, Kelly M, et al. Health-education to prevent COVID-19 in schoolchildren: a call to action. Infect Dis Poverty. 2020 Jul 1;9:81. doi: 10.1186/s40249-020-00695-2. [Google Scholar][Pubmed] Rosas-Blum ED, Granados HM, Mills BW, Leiner M. Comics as a Medium for Parent Health Education: Improving Understanding of Normal 9-Month-Old Developmental Milestones. Front Pediatr. 2018;6:203. doi: 10.3389/fped.2018.00203[Google Scholar][Pubmed] Pratama DM, K Kasmana. The Indonesian Government Imagery in the Instagram Comic strip with Covid-19 Themed [Internet]. 2020. Available from: https://icobest.unikom.ac.id/submission/proceeding/download/122 McNicol S. The potential of educational comics as a health information medium. Health Information & Libraries Journal. 2017;34(1):20–31. doi: 10.1111/hir.12145[Google Scholar][Pubmed] Ghia JE, Gaulin S, Ghia L, Garancher L, Flamand C. Informing children citizens efficiently to better engage them in the fight against COVID-19 pandemic. PLOS Neglected Tropical Diseases. 04 Nov 20;14(11):0008828. doi: 10.1371/journal.pntd.0008828.[Google Scholar] [PMC free article] [Pubmed]